Navigating Political Dynamics and Health Inequities: Challenges to Precision Medicine in a Rural Health Setting - Sarong, Kim G. (Silliman Journal, 2024)
In this era of dramatic, rampant, and incessant political change, predictions about the future can no longer be based either on conventional wisdom or historical precedent. We are, after all, in the middle of a paradigm shift that is shredding prognosticators and their prognostications with voraciousness – especially in the acquisition and distribution of health services to the consumers. Health status has improved dramatically in the Philippines over the last 40 years: infant mortality has dropped by two- thirds, the prevalence of communicable diseases has fallen and life expectancy has increased to over 70 years. However, considerable inequities in health care access and outcomes between socio-economic groups remain. Thus, this paper primarily sought to investigate and determine the barricades and challenges towards the attainment of precision medicine in small-scale locale study. This qualitative study utilized small group discussions, key informant interviews, and review of secondary data. Thematic and case analysis were utilized by the researcher to analyze data as deemed and provided by the respondents. Results were based on political history and dynamics, municipal health budget, implementation of programs via the municipal or rural health unit and linkage between the municipal health sector and local government unit. Overall, delivery of health services to the public was being compromised since health workers were less knowledgeable, undertrained, and underpaid and received minimal budget allotment, consequently leading to an imprecise delivery of health goods.